Leningrad Printed Fabrics Production: From Serial Samples to Art Objects - Shirokovskikh, Margarita S. (Actual Problems of Theory and History of Art, 2018)
The article reflects the results of the study on the printed fabrics produced by the Vera Slutskaya factory. It also addresses the actual questions of textile design. The described tissue samples and patterns were provided by museums and private collections. Certain examples of the creative practice of the design artists Irina Alova and Irina Ikonnikova are presented in the article. An attempt has been made to consider the printed fabric, not only as the result of the production process, but as part of the city’s cultural potential. The studied volume of the materials made it possible to reveal the specific features of the textile patterns and to identify the authors of the repeated ornaments. The recommendations of VIALegprom (The All-Union Institute of the Assortment of Products of Light Industry and Clothing Culture) have been compared with the museum collections and archives, which resulted in the specification of the main thematic trends of the design of Leningrad industrial textiles of the last third of the 20th century. Finally, the main tendencies in the development of the printed ornament in the spirit of the 1980s and 1990s have been determined, and the increasing influence of fashion has been underlined.
Keywords: textile factory; fabrics; printed pattern; design; Leningrad; State Museum of History of St. Petersburg; ornament; batiste; marquisette